Study of Polyphenol Content and Antioxidant Capacity of Myrianthus Arboreus (Cecropiaceae) Root Bark Extracts - Pierre Betu Kasangana; Pierre Selim Haddad; Tatjana Stevanovic (Antioxidants, 2015)
In order to evaluate the therapeutic potential of polyphenolic extracts from root bark of M. arboreus, we have determined the content of various polyphenols in aqueous and ethanol (EtOH) extract as well as two sub-fractions of the latter: ethyl acetate (EAc) and hexane (Hex). The total phenols, flavonoids, hydroxycinnamic acids and proanthocyanidins have been determined for all studied extracts/fractions by spectrophotometric methods. Both TP content (331.5 ± 2.5 mg GAE/g) and HCA content (201 ± 1.5 mg CAE/g) were determined to be the highest in EAc fraction of EtOH extract. All studied extracts were however determined to have a low content in flavonoids. The determination of antioxidant capacities of the studied extracts has also been performed by the following in vitro antioxidant tests: DPPH scavenging, phosphomolybdenum method and oxygen radical absorbance (ORACFl and ORACPRG) assay. The results of the DPPH free radical and ORACFl assays showed that there is no significant difference between the EAc fraction and Oligopin®, but the EAc fraction exhibited the highest antioxidant capacity as determined by the phosphomolybdenium method. In addition, the EtOH extract was determined to have the same antioxidant efficiency as the synthetic antioxidant BHT or commercial extract Oligopin® by phosphomolybdenum method. On the other hand, a positive correlation (r < 0.6) was found between different classes of polyphenols and the results of the phosphomolybdenum method, ORACFl as well as ORACPRG, except for the DPPH assay, for which a negative correlation was indicated (r < 0.62). Interestingly, it seems that the content in hydroxycinnamic acids played a big role in all assays with r < 0.9. According to the present study, EAc fraction and EtOH extract should be further studied for the potential use in the pharmaceutical and food industry.